Realization of microfluidic devices with steel displacement amplifiers for cell culturing and analysis - İşeri, Emre. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
In this thesis, micro uidic devices with simple trapping mechanism which can be actuated by applying force to use them for cell culturing and analysis applications are designed, analyzed and fabricated. Steel displacement ampli ers are designed, analytically evaluated and simulated to use them as trapping mechanism in micro uidic channels. In addition, analytical model of the hydrodynamic resistance of device and the results of the ow simulations are discussed in order to describe and characterize the device. 50 m-thick steel thin lms, 1 mm-thick Poly methyl methacrylate (PMMA) plates, and 125 m-thick Polyethylene naphthalate (PEN) lms are used to realize the device. Fabrication methods, which are photolitography, electrochemical etching, wet etching, hot embossing, thermo-compression bonding and laser micromachining are illustrated. Electrochemical etching process is characterized. Results of displacement measurements of the steel displacement ampli er under di erent loads is presented . Coe cient of thermal expansion (CTE) di erence problem that is encountered during hot embossing process of steel and PMMA is discussed. It is shown that using PEN substrates which have almost same CTE as the steel thin lms solve the CTE mismatch issue. In conclusion, the nal version of the fabricated device is presented. Moreover, necessary studies in order to actuate steel displacement ampli er embedded in micro uidic channel are discussed as a future work.
Keywords: Cell culture.; Microfluidic devices.